Pemuda (Pe)kerja Paruh Waktu: Dependensi dan Negosiasi - Nanda Harda Pratama Meiji (Jurnal Studi Pemuda, 2019)
Part-time work is a relatively common thing for young people today. Unlike the previous decade, now, part-time jobs offered are mushrooming with various types of activities. Similarly, Indonesia offers a variety of part-time jobs to its main students. Malang, a city of education with thousands of students in it, also competing to take part in working part-time. This study seeks to focus on the aspects of dependency and negotiation carried out by students who take part-time jobs, especially at coffee shops. This phenomenon is because the culture of "coffee" has become one of the activities carried out by young people in Indonesia to spend their free time. Not only limited to hanging out, but also the coffee culture is also used by young people in Malang City in addition to looking for financial and experience additions before taking the post-graduate work pathway. This study used qualitative research methods with the process of observation and in-depth interviews to informants in the field as a technique of data collection. Through a purposive sampling process, four main informants were able to present their narratives while working part-time while working on their final assignments. This research was conducted from mid-2018 to 2019 to obtain sufficient depth. From the results of this study it was found that there is a close relationship between the process of dependencies that they do with negotiation and consumption during part-time work. Especially entering the era of the risk society where every decision that has been taken will pose risks that must be passed and minimized the danger by young part-time workers.